A COGNITIVE-METAPHORICAL ANALYSIS OF THE CONCEPT OF “LOVE” IN THE EXPLANATORY DICTIONARY OF THE UZBEK LANGUAGE - Sojida Abdukhakimova (International Journal of Literature and Language Studies, 2026)
Abstract: This article investigates the cognitive-metaphorical properties of the concept of “love” in the Uzbek language based on the conceptual metaphor theory developed by J. Lakoff and M. Johnson. The research material includes lexical units from the Explanatory Dictionary of the Uzbek Language and illustrative examples drawn from literary texts. The study demonstrates that the concept of love is structured through several dominant source domains, including PRECIOUS OBJECT, PLANT, FIRE, ILLNESS, and EXCHANGE. Each metaphorical model reveals different semantic dimensions of love, such as value and worth, development and growth, emotional intensity, psychological suffering, and socio-ethical evaluation. The findings indicate that, within Uzbek linguocultural cognition, the concept of love constitutes a multilayered and dynamic cognitive structure formed through systematic metaphorical mappings between abstract emotional experience and concrete source domains.